Pengaruh Performance Mahasiswa PPL terhadap Peningkatan Hasil Belajar Fisika Siswa di SMA - Faradiba Faradiba (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2016)
Research has conducted student teachers’s performance influence to improving student’s learning outcomes in high school in August 2015 - January 2016. The study was conducted with 4 phases: (1).Providing pretest, posttest and questionnaires. (2). Data collection pretest, posttest and questionnaires. (3). Data processing such as coding and simple regression model . (4). Simple regression analysis and variable presentation supporting student’s learning. The correlation coefficient 0.712 (71.2%) for the relation between the two variables categorized strong. Determasi coefficient value of 0, 507 (50.7%) which describe student teacher’s performance (X) has the effect of a contribution of 50.7% to the student’s learning outcomes (Y) and 49.30% influenced by other factors. Regression model Y = -43.507 + 2,887X.T test obtained Thitung 10,69 greater than Ttable 1.98 which mean that there is influence student teacher’s performance toward improving student learning outcomes. F test obtained Fhitung 115.23 value greater than Ftable which mean the model is expressed well.